Sensory evaluation and nutritional information on organic brown rice - David, Wahyudi; Ardiansyah; Budijanto, Slamet; Strassner, Carola (Organic agriculture, 2020)
Rice milling mode (brown and polished rice) creates a dilemma for organic brown rice (OBR) where the nexus is between consumer preference and nutritional properties. The appearance of rice is often considering an important attribute for consumers. Based on this, the present study examines the effect of nutritional information to the consumer preference of OBR. Forty university students have been recruited based on interest and availability. The subjects have been divided into two groups: A (nine males and 11 females) and B (seven males and 13 females), as per the order of information and non-information about the nutritional benefits of consuming OBR. Questionnaires to examine the quality concept of organic rice before and after the treatment have been prepared. ISO 13299, 2016 has been applied to establish a sensory profile. The single list attributes (taste, aroma, colour, and texture) have been used to examine panellist responses. Two varieties of long-grain organic rice have been prepared in the two-milling mode (brown and polished). This study reveals that the nutritional information of brown rice affects panellist responses on colour and texture. For the un-informed group B, colour and texture attributes were considered lower for brown rice compared with polished rice, while for the informed group A, there were no significant differences of these quality attributes between both rice types. The intervention of nutritional information seems to improve the lower brown rice attributes.